Concerns and strategies of parents in relations with teenagers - Costin, Alina (Technium Social Sciences Journal, 2025)
There is a lack of systematic knowledge regarding parents’ concerns and worries about adolescents’ experiences. In recent years, cracks have been reported in the construction of the parent-adolescent dialogue (Montemayor, 1983; Runcan, 2020;. Huver et al., 2010; Patterson, Forgatch, 1987), in the sense that parents consistently report facing difficulties in managing their relationship with their adolescent children. Beyond generational differences, parent-adolescent relationships today seem to be more dynamic and complex than ever before (Chalasani, 2007; Iosim et al., 2022). Therefore, in this preliminary study, we aim to explore this topic by examining the opinions of parents of adolescents regarding the areas in which they face difficulties, their concerns about their relationship with their child or adolescent, and the principles they implement in parenting. A total of 80 participants in a qualitative study were grouped into 8 focus groups based on: a) belonging to a two-parent or single-parent family, and b) level of education. Thematic analysis allowed the identification of several recurring themes and particularities in the case of single parents regarding the challenges in their relationship with their adolescent child. Significant differences were observed in the approach to parent-adolescent relationships between single parents and those from two-parent families. The implications of these differences were discussed in shaping parental education programs.